2011
DOI: 10.1155/2011/582945
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and Hepatitis C Infection Biomarkers and TP53 Mutations in Hepatocellular Carcinomas from Colombia

Abstract: Hepatocellular Carcinoma (HCC) is a leading cause of cancer-related death worldwide. Globally, the most important HCC risk factors are Hepatitis B Virus (HBV) and/or Hepatitis C Virus (HCV), chronic alcoholism, and dietary exposure to aflatoxins. We have described the epidemiological pattern of 202 HCC samples obtained from Colombian patients. Additionally we investigated HBV/HCV infections and TP53 mutations in 49 of these HCC cases. HBV biomarkers were detected in 58.1% of the cases; HBV genotypes F and D we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
6
0
7
Order By: Relevance
“…Further, specific epigenetic processes may be affected by aflatoxins, especially during a prolonged period of exposure, promoting tumorigenesis, angiogenesis, invasion and metastasis to other organs in cases of hepatocellular carcinoma (Bbosa et al 2013). In a study conducted in Colombia, 10.5% of 202 HCC cases had the characteristic aflatoxin-induced mutation of codon 249 of the p53 tumour suppressor gene (Navas et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Further, specific epigenetic processes may be affected by aflatoxins, especially during a prolonged period of exposure, promoting tumorigenesis, angiogenesis, invasion and metastasis to other organs in cases of hepatocellular carcinoma (Bbosa et al 2013). In a study conducted in Colombia, 10.5% of 202 HCC cases had the characteristic aflatoxin-induced mutation of codon 249 of the p53 tumour suppressor gene (Navas et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They include TNF- α , TGF β , PGF, and other factors contributing towards the fibrogenesis [ 5 , 6 ]. Among these, TNF- α is the most important cytokine in host immune response to viral infection [ 7 , 8 ]. TNF- α is a pleiotropic cytokine, located 850 kb telomeric of class II HLA-DR locus of the short arm of chromosome 6, which induces cellular responses such as proliferation, production of inflammatory mediators, and cell death [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…(20) In Colombia, the R249S mutation was found in only 4 of the 38 HCC cases (11%), with twenty-five of the cases being positive for HBV infection. (22) In Mexico, 18% of HCC samples (3/16) had the AFB 1 -signature mutation, with only 3 cases being positive for HBV. 21As maize is commonly consumed in a number of Latin American countries, exposure to AFB 1 is likely.…”
Section: Discussionmentioning
confidence: 99%
“…(12)(13)(14)(15)(16)(17)(18)(19) In the Americas, the R249S mutation prevalence reportedly ranges between 10.5% and 28%. (20)(21)(22) In the U.S., a recent study reported that 7% of the HCCs among Hispanic patients in southern Texas had the R249S mutation. (23) No studies have been previously conducted in northern Central America, a region characterized by high AFB 1 exposure, but low prevalence of chronic HBV infection.…”
Section: Introductionmentioning
confidence: 99%